(untitled) - Toynbee, Arnold (New York, 1957)
Acknowledged as one of the greatest achievements of modern scholarship, Arnold Toynbee's A Study of History is a ten-volume analysis of the rise and fall of human civilizations. Contained in two volumes, D.C. Somervell's abridgement of this magnificent enterprise preserves the method, atmosphere, texture, and, in many instances, the very words of the original. First published in 1947 and 1957, these two volumes are themselves a great historical achievement. Volume 2, which abridges Volumes VII-X of Toynbee's study, includes sections on Universal States, Universal Churches, Heroic Ages, Contacts Between Civilizations in Space, Contacts Between Civilizations in Time, Law and Freedom in History, The Prospects of the Western Civilization, and the Conclusion.
Keywords: Văn minh,Civilization